Genome-wide association mapping of flowering time in Arabidopsis thaliana in nature: genetics for underlying components and reaction norms across two successive years - Brachi, Benjamin (2013)
Often used as a proxy for the transition to reproduction, flowering time (FT) is an integrative trait of two successive biological processes, i.e. bolting time (BT) and the interval between bolting and flowering time (INT). In this study, we aimed to identify candidate genes associated with these composite traits in Arabidopsis thaliana using a field experiment. Genome-wide association (GWA) mapping was performed on BT, INT and FT based on a sample of 179 worldwide natural accessions genotyped for 216,509 SNPs. The high resolution conferred by GWA mapping indicates that FT is an integrative trait at the genetic level, with distinct genetics for BT and INT. BT is shaped largely by genes involved in the circadian clock whereas INT is shaped by genes involved in both the hormone pathways and cold acclimation. Finally, the florigen TSF appears to be the main integrator of environmental and internal signals in ecologically realistic conditions. Based on FT scored in a previous field experiment, we also studied the genetics underlying reaction norms across two years. Only four genes were common to both years, emphasizing the need to repeat field experiments. The gene regulation model appeared as the main genetic model for genotype × year interactions.